Hasonlóságok és különbségek a pályázati projektek sikerében - az Ausztria-Magyarország határon átnyúló együttműködési program sikervizsgálata (Similarities and Differences in the Success of the Tender Projects – the Success Analysis of the Projects Implemented in the Austria-Hungary Cross-Border Program - Zoltán Birkner; Nikoletta Kaszás; Tamás Kovács; Kornél Németh (DETUROPE)
Since the 1990s the European Union has paid more and more attention to subsidising cross-border developments. Cross-border co-operations are of outstanding importance since the length of the state border is comparatively large and a significant part of the Hungarian inhabitants live in the border region (Horváth, 2002). In the course of our research we studied the success of projects in the frame of the Austria-Hungary Cross-border Cooperation Programme 2007-2013. After a brief introduction of the special characteristics of the border region and cross-border programs our aim was to explore the factors by which the success of the tender projects can be measured. Based on the empirical research we conducted that the success of the projects in the studied program can be measured through the time factor, the project management success and the satisfaction of the target groups. We also examined in what proportion the studied organizations can be considered as successful based on these success factors; and what kind of groups, clusters can be developed from them.